Hypercapnea and Acidemia despite Hyperventilation following Endotracheal Intubation in a Case of Unknown Severe Salicylate Poisoning - Shannon M. Fernando; Valérie Charbonneau; Hans Rosenberg (Case Reports in Critical Care)
Salicylates are common substances for deliberate self-harm. Acute salicylate toxicity is classically associated with an initial respiratory alkalosis, followed by an anion gap metabolic acidosis. The respiratory alkalosis is achieved through hyperventilation, driven by direct stimulation on the respiratory centers in the medulla and considered as a compensatory mechanism to avoid acidemia. However, in later stages of severe salicylate toxicity, patients become increasingly obtunded, with subsequent loss of airway reflexes, and therefore intubation may be necessary. Mechanical ventilation has been recommended against in acute salicylate poisoning, as it is believed to take away the compensatory hyperpnea and tachypnea. Despite the intuitive physiological basis for this recommendation, there is a paucity of evidence to support it. We describe a case of a 59-year-old male presenting with decreased level of consciousness and no known history of ingestion. He was intubated and experienced profound hypercarbia and acidemia despite mechanical ventilation with high minute ventilation and tidal volumes. This case illustrates the deleterious effects of intubation in severe salicylate toxicity.